PEMANFAATAN MEDIA SOSIAL DALAM PROMOSI POTENSI WISATA BAHARI CILACAP JAWA TENGAH - Yuni Tresnawati (Universitas Muhammadiyah Jakarta, 2018)
Social networking sites or social media today is already familiar to the public, almost every individual using social media from the young to the old either for bussiness or just to connect with friends. One positive impact is as a communication medium can facilitate the search for information. For example many who use social media search for news that is actual or even looking for a trendy tourist destination through uploads of users of social media. This can indirectly assist the promotion of tourist attractions. Therefore, this study will discuss more deeply about Social Media Utilization in Promotion of Marine Tourism Potential in Cilacap , Central Java . The concepts used are the utilization of social media and marketing communications and 7 C Framework Communication using constructivist paradigm with qualitative descriptive approach. The proper use of social media includes persuasion and emotional attachment to increase trust of followers of the account against the information provided. The development of world tourism is very rapid, making Indonesia be left behind by continuing to improve tourism in this country. Although Indonesia's tourism contribution continues to increase every year, it still needs to be improved so as not to be left behind from other countries whose tourism is also growing. Increased one of them is to attract more tourists (both abroad and archipelago) to Indonesia. The way to go is of course through promotion. Therefore, the improvement of innovation in the field of promotion must continue to be done.Keywords: Digital, Social Media, Promotion, Tourism